Effects of Feeding Nozzle and Cup Feeding on Reaching the Time of Full Oral Feeding in the Premature Infants in the Neonatal Intensive Care Unit - Sara Rahmani; Amir Mohammad Armanian; mahboobeh namnabati (Mashhad University of Medical Sciences, 2018)
Background: Oral feeding problems are among the most common issues in preterm infants. Various methods and feeding support tools are used in this regard, such as cup feeding and feeding nozzle. The present study aimed to determine the preferred method between cup feeding and feeding nozzle to support oral feeding in premature neonates. Methods: This clinical trial was conducted on 70 preterm infants with the gestational age of 30-33 weeks in Isfahan, Iran. Infants were divided into two groups of cup feeding and feeding nozzle application. The studied variables were the duration needed to reach the time of full oral feeding, weight changes since birth until full oral feeding, and length of hospital stay. Results: Mean duration to start full oral feeding was 4.03 and 5.1 days in the cup feeding and feeding nozzle groups, respectively (P0.05). Mean length of hospital stay was 23.1 and 21.9 days in the cup feeding and feeding nozzle groups, respectively (P>0.05). Conclusion: According to the results, the time needed to reach full oral feeding was shorter in the cup feeding group compared to the feeding nozzle group. However, the mean length of hospital stay was two days shorter in the feeding nozzle group compared to the cup feeding group. Therefore, feeding nozzle could be utilized as a supportive method in the feeding of preterm infants.